2000
DOI: 10.1093/emboj/19.24.6759
|View full text |Cite
|
Sign up to set email alerts
|

A novel ability of Smad3 to regulate proteasomal degradation of a Cas family member HEF1

Abstract: Smad3 is a key signal transducer of transforming growth factor-b (TGF-b) and activin, and is known to be a DNA-binding transcriptional regulator. Here we report a novel property of Smad3 in regulating the proteasomal degradation of the human enhancer of ®lamentation 1 (HEF1), which is a member of the Cas family of cytoplasmic docking proteins. Our studies revealed that Smad3 interacts with HEF1 and triggers the proteasomal degradation of HEF1 in overexpression systems. In addition, TGF-b stimulation induces ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 21 publications
5
91
0
Order By: Relevance
“…5B). Recent published works agree with the preferential degradation of p115HEF1 isoform [16,18], although no kinase was identified yet. Interestingly, haematopoietic isoform of Cas/HEF1 Associated signal Transducer (CHAT-H), a binding partner of the Cas family proteins, is required to induce ser/thr phosphorylation of HEF1 and N-terminal domain of CHAT-H is necessary for this phosphorylation to occur [11].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…5B). Recent published works agree with the preferential degradation of p115HEF1 isoform [16,18], although no kinase was identified yet. Interestingly, haematopoietic isoform of Cas/HEF1 Associated signal Transducer (CHAT-H), a binding partner of the Cas family proteins, is required to induce ser/thr phosphorylation of HEF1 and N-terminal domain of CHAT-H is necessary for this phosphorylation to occur [11].…”
Section: Discussionmentioning
confidence: 80%
“…Several reports demonstrated that ser/thr phosphorylation of HEF1 mediates its proteasomal degradation; p115HEF1 being the main isoform interacting with Smad3 and triggering the degradation of both proteins via an APC/CDH1 pathway [16,17]. Moreover AIP-4, an E3 ubiquitin ligase for HEF1, interacts more strongly with p115HEF1 than with the p105 isoform and ectopic expression of AIP-4 triggers preferentially p115HEF1 degradation [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smads regulate gene expression by a variety of mechanisms, including recruitment of transcriptional coactivators such as CREB binding protein (CBP)/p300 (33-36) (37) as well as transcriptional corepressors, such as 5ЈTG3Ј interacting factor, Ski, and SnoN (38 -43). Recent studies have revealed that Smads can also regulate the stability of Smad nuclear interacting protein 1, a nuclear repressor of CBP/p300 (44,45), and the cytoplasmic signaling protein human enhancer of filamentation 1 (46).…”
Section: Uncoupling Of Promitogenic and Antiapoptotic Functions Of Ilmentioning
confidence: 99%